STRATEGI YAYASAN REYOG PONOROGO INDONESIA UNTUK KELANGSUNGAN KESENIAN REYOG PONOROGO PROVINSI JAWA TIMUR - Riyadi, Sigit Wahyu; Pramono, Joko; Haryanto, Aris Tri (JI@P, 2023)
Reyog Ponorogo is a legacy of works of art from the ancestors of the Indonesian nation that has survived centuries until now is still able to survive because Reyog Ponorogo has a very important function and role in people’s lives in Ponorogo. The purpose of this research is to describe the strategies and obstacles of the Reyog Ponorogo Foundation in the continuity of the Reyog Ponorogo arts. The results of the research show that the S-O Strategy, namely the Art of Reyog Ponorogo, is the final form of a long development process that contains philosophical, religious and educational values that need to be preserved. The ST (Strenghts-Threats) Strategies for Reyog Development that have been collected are: 1) Building a system of "inheritance" and regeneration of Konco Reyog Ponorogo, 2) Organizing Routine Exercises and Performances, 3) Maintaining Standards, 4) Emphasizing Stories in Playing Reyog, 5) Building community and government support, 6) Integrating Reyog in Ponorogo Culture and Tourism Promotion. WT (Weaknesses-Threats) Strategy An original regional art that is second to none in other regions and is now known by the wider community to the international scene. The WT (Weaknesses-Threats) strategy, Reyog which is the main attraction of Ponorogo Regency is preserved by holding reyog performances every full moon, reyog festival every year which is summarized in the grebeg suro event and Ponorogo anniversary. Keyword : Reyog Ponorogo Foundation, Art of Reyog Ponorogo.